Pengaruh penambahan daun pohon terhadap kadar VFA dan kecernaan secara in-vitro ransum berbasis ketela pohon (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this researchwasto findthe effect oftree leaves added into acassava biomass based ration on VFA concentration and in-vitro digestibility. This research used a randomized block design with 4 treatmentsand 3 groupsof replications. Feed treatment was composed by20% of cassava meal + 30% of cassava peel silage meal + 50% of leaf meal. P1was Manihot uttilissima leaf meal, P2was Gliricidia sepium leaf meal, P3was Moringa oleifera leaf meal and P4was Tectona grandis leaf meal. In-vitro incubation time was 48 hours in the syringe. The result showed that the value of gas production at hours12 hadsignificant differences(P<0.05) onthe treatments, with the highest values in P3. Gas production values ​​were significantlydifferent (P<0.01) at hours 24and 48. Theaveragedry matter digestibility (DMD)and in-vitro organic matter digestibility (OMD)was found the highest in P1 and P3. The highest VFA concentration was found in P3. The treatment had highlysignificanteffect (P<0.01) on the concentration of acetic acid (C2) andhad significant differences (P<0.05) on the concentrationofpropionic acid (C3),butyric acid (C4)and C2/C3 ratio. The concentration of CO2 and CH4 did not give significant differences (P>0.05). Theconclusion ofthis research was the addition of Manihot uttilissima leafmealand Moringa oleifera leaf meal was the best addition in cassava-based feedof that reviewedby in-vitro. Keywords: Cassava, in-vitro, gas production, leaf meal